SOSIALISASI PENTINGNYA PAJAK UMKM UNTUK MENINGKATKAN KONTRIBUSI PENDAPATAN NEGARA - Edon Ramdani; Satiman Satiman; Suparmin Suparmin (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2022)
Tax is one of the sources of state revenue. Through levies/tax levies obtained by the state, the proceeds or funds from the applied taxes are then used to build facilities and infrastructure to support the economy and the welfare of the community. UMKM sector is one of the tax objects that is expected to contribute to state revenue. UMKM have a very large contribution to Indonesia's Gross Domestic Product (GDP), reaching 60% or around Rp. 2 trillion. UMKM are also able to employ as many as 97 percent of the workforce of a total of 64 million in Indonesia. Unfortunately, it contribution to state revenue from taxes is still very small compared to these figures. Based on data from the Directorate General of Taxes at the Ministry of Finance (2019), the contribution of the final PPh of UMKM amounted to Rp. As the name implies, Micro, Small and Medium Enterprises (MSMEs) are businesses with relatively small capital. The main capital of MSMEs is creativity and human resources. Most of them also have bookkeeping or administration which is still less organized and effective. Even so, MSMEs are the foundation of the Indonesian economy. One of the causes of the less tax contribution of MSMEs is because their ability to do books and undergo tax administration is still lacking. This makes it difficult for them to carry out their obligations as taxpayers. In addition, many micro-scale businesses in Indonesia do not understand financial statements and taxation, so the contribution of MSMEs to taxes is still small. Based on this condition, our Accounting Lecturer at Pamulang University took the initiative to socialize the importance of MSME Tax for state income. Our PKM is carried out directly on MSME business actors and the socialization is carried out at the Sate and Duck Soup Culinary Business Hj. Siti, in Sapatan Tangerang. The purpose of this PKM is to provide business actors with a broader understanding of MSME taxes.